Hypoxia-Conditioned MSC Exosomes Upregulate mTORC1 and Suppress MMP-2 in a UV-B–Induced Collagen Loss Rat Model - Fadhillah, Anggrila Sekar; Putra, Agung; Sumarawati, Titiek; Setiawan, Eko (Molecular and Cellular Biomedical Sciences, 2026)
Background: Ultraviolet-B (UV-B) radiation accelerates photoaging by disrupting extracellular matrix (ECM) homeostasis through dysregulation of mechanistic target of rapamycin complex 1 (mTORC1) and upregulation of matrix metalloproteinase-2 (MMP-2). This study evaluated the effects of exosomes of hypoxia-conditioned mesenchymal stem cells (EH-MSCs) on mTORC1 and MMP-2 expression in a UV-B–induced collagen loss rat model.Materials and Methods: Thirty male Wistar rats were randomized into five groups: healthy control, UV-B + saline, UV-B + hyaluronic acid, UV-B + 200 µL EH-MSCs, and UV-B + 300 µL EH-MSCs. Collagen loss was induced by UV-B irradiation for two weeks (10 sessions, 8 min/session). A single treatment was administered on day 22, and tissue was collected on day 29. Exosomes were isolated from hypoxia-conditioned MSCs and characterized by morphology and surface markers. Gene expression of mTORC1 and MMP-2 was assessed by qRT-PCR and analyzed using one-way ANOVA.Results: UV-B exposure induced collagen loss histologically. EH-MSCs significantly increased mTORC1 expression, highest in the 300 µL group (p < 0.001), and reduced MMP-2 expression, lowest in the 300 µL group.Conclusion: EH-MSCs exert dual regulatory effects by upregulating mTORC1 and suppressing MMP-2 in UV-B–induced collagen loss, suggesting therapeutic potential to mitigate photoaging via anabolic signaling (via mTORC1) and reduced ECM degradation (via MMP-2).Keywords: collagen loss, exosomes, MMP-2, mTORC1, UV-B